2018
DOI: 10.1155/2018/5416725
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Characteristics of Lactic Acid Bacteria Isolated from Homemade Fermented Foods

Abstract: Objective. Lactic acid bacteria (LAB) were isolated from fermented foods, such as glutinous rice dough, corn noodle, chili sauce, potherb mustard pickles, and stinky tofu, in northeast China. LAB strains with antimicrobial activities were screened, and seven of these Lactobacillus strains were identified as L. plantarum, L. pentosus, and L. paracasei through 16S rRNA gene analysis. After the supernatant of LAB was treated with proteinase K, pepsin, and papain, their antibacterial effect almost disappeared. Mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 28 publications
4
40
2
Order By: Relevance
“…bacteria, demonstrating a decrease of antibacterial action with proteinase K and pronase treatment of the bacteriocin, but not due to α-amylase treatment. The bacteriocins of L. plantarum, L. pentosus and L. paracasei displaying growth inhibitory effect against Salmonella and S. aureus with ZDIs 13.08±0.15-15.22±0.13 mm, lost their antimicrobial action after treatment with proteolytic enzymes (proteinase K, pepsin, and papain), as has been reported by Ren et al (2018). In the current study, on enzymatic treatment with proteinase K and trypsin, the L. fermentum LMEM22 bacteriocin activity has been found to be decreased when tested against grampositive (Staphylococcus aureus and Listeria monocytogenes) as well as gram-negative (Acinetobacter baumannii and Escherichia coli) indicator bacteria, and the bacteriocin was found insensitive against αamylase activity, authenticating its proteinaceous nature, which was in accordance to the report of the earlier authors (Ge et al, 2016;Fahim et al,, 2017).…”
Section: Discussionsupporting
confidence: 68%
“…bacteria, demonstrating a decrease of antibacterial action with proteinase K and pronase treatment of the bacteriocin, but not due to α-amylase treatment. The bacteriocins of L. plantarum, L. pentosus and L. paracasei displaying growth inhibitory effect against Salmonella and S. aureus with ZDIs 13.08±0.15-15.22±0.13 mm, lost their antimicrobial action after treatment with proteolytic enzymes (proteinase K, pepsin, and papain), as has been reported by Ren et al (2018). In the current study, on enzymatic treatment with proteinase K and trypsin, the L. fermentum LMEM22 bacteriocin activity has been found to be decreased when tested against grampositive (Staphylococcus aureus and Listeria monocytogenes) as well as gram-negative (Acinetobacter baumannii and Escherichia coli) indicator bacteria, and the bacteriocin was found insensitive against αamylase activity, authenticating its proteinaceous nature, which was in accordance to the report of the earlier authors (Ge et al, 2016;Fahim et al,, 2017).…”
Section: Discussionsupporting
confidence: 68%
“…Concerning Gram-positive bacteria, the most suppressive effect was detected in the case of Staphylococcus aureus, with a large inhibition zone of 16.63 mm in the case of the CCP 10-1/1 iso-late. The characterized LAB isolates from sausages exerted greater inhibitory effect against S. aureus in contrast with bacterial isolates from home-made fermented foods (Ren et al, 2018). In the case of the two Bacillus strains, the inhibition zone ranged between 11.40 and 14.40 (B. cereus) and between 8.6 and 14.53 (B. subtilis).…”
Section: Resultsmentioning
confidence: 90%
“…Ren et al . [ 32 ] found that Lactobacillus T8 produced antibacterial substances belonging to a protein family, and its zone of inhibition against pathogens significantly increased (>13 mm) after these substances were produced. Obdak et al .…”
Section: Resultsmentioning
confidence: 99%